Pharyngocutaneous fistula in a Glottic carcinoma: A rare initial presentation - Tiwari, Disha; Shah, Manjari; Barthwal, Mansi; Pandey, Amit; Yadav, Arun Kumar; Singh, Alankrita; Yadav, Dev Kumar; Bhatt, Madan Lal Brahma (Asian Journal of Medical Sciences, 2017)
Pharyngo-cutaneous fistula is a well-known complication following total laryngectomy in case of carcinoma larynx, however it is a very rare entity to present as an initial and sole presentation of carcinoma glottis. Here we are reporting case of glottic carcinoma presented to us with pharyngo-cutaneous fistula as an initial presentation. Asian Journal of Medical Sciences Vol.8(6) 2017 42-44